2021
DOI: 10.1177/1098612x211041307
|View full text |Cite
|
Sign up to set email alerts
|

Perception of stress in cats by German cat owners and influencing factors regarding veterinary care

Abstract: Objectives Visiting the veterinarian is generally perceived as a stressful situation for cats. Previous studies have shown that the perception of stress may influence cats’ healthcare. In order to minimise stress in cats during the veterinary consultation, feline-friendly handling has gained importance and is increasingly being used. The aim of this study was to find out whether cats experience stress during a visit to the veterinarian (and, if so, to what extent), and which factors influence the perception of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
0
6
1
Order By: Relevance
“…35 While cats that exhibited aggression at the veterinary clinic were more likely to receive medications and/or supplements intended to reduce fear, anxiety and/or pain before veterinary visits in this study, the majority (66.9%) of cats did not receive an anxiolytic before their most recent veterinary visit. Given that most cats are stressed during veterinary visits, [1][2][3][4][5][6] this suggests a missed opportunity for veterinarians to reduce veterinary visit-related stress in cats. This is especially important given that a recent study found that the majority of companion cat owners reported that they would or might consider giving psychoactive medications to their cats, particularly situational anti-anxiety medications, but only half of the owners were aware of the availability of psychoactive medications for cat behavior problems.…”
Section: Discussionmentioning
confidence: 99%
“…35 While cats that exhibited aggression at the veterinary clinic were more likely to receive medications and/or supplements intended to reduce fear, anxiety and/or pain before veterinary visits in this study, the majority (66.9%) of cats did not receive an anxiolytic before their most recent veterinary visit. Given that most cats are stressed during veterinary visits, [1][2][3][4][5][6] this suggests a missed opportunity for veterinarians to reduce veterinary visit-related stress in cats. This is especially important given that a recent study found that the majority of companion cat owners reported that they would or might consider giving psychoactive medications to their cats, particularly situational anti-anxiety medications, but only half of the owners were aware of the availability of psychoactive medications for cat behavior problems.…”
Section: Discussionmentioning
confidence: 99%
“…A minimum annual wellness examination is recommended for cats by veterinarians and veterinary organizations ( Hoyumpa Vogt et al., 2017 ). However, owners may avoid visits to a veterinarian if they know their cat will behave aggressively during a health examination or if they consider health examinations stressful for their cat ( Karn-Buehler and Kuhne, 2021 ). However, it is also possible that cats that rarely visit the veterinarian may have undiagnosed health problems that cause pain, leading to aggressive behavior ( Amat and Manteca, 2019 ; Mills et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, as fearfulness is heritable ( Salonen et al., 2019 ), breeders may, in theory, decrease the average fearfulness by preferring non-fearful parents in breeding. However, signs of fear in cats are much harder to identify than aggression, at least for the owners ( Karn-Buehler and Kuhne, 2021 ), and no easy and effective tools are available for breeders to evaluate the fearfulness or other personality traits of their breeding individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that most of these owners noted other signs of stress in their cat during the lead up to and after the consultation highlights that it is not simply the consultation itself that is a source of stress. The importance of reducing stress in cats requiring veterinary attention has been highlighted by another recent study, 8 and should focus on all stages of the visit, including whether the visit should be face to face or virtual; how owners can help make travel less stressful for their cat; the waiting room experience; and the consultation itself.…”
Section: Discussionmentioning
confidence: 99%